2019
DOI: 10.1055/a-0767-7063
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality in der Augenheilkunde: Technische Innovation ergänzt studentische Lehre

Abstract: Zusammenfassung Hintergrund An der Medizinischen Fakultät der Universität Ulm werden die Lernziele der Augenheilkunde den Studierenden schwerpunktmäßig in einer einwöchigen Blockveranstaltung im 4. Studienjahr vermittelt. Gemäß des Nationalen Kompetenzbasierten Lernzielkatalogs Medizin (NKLM) zählt zu diesen Lernzielen auch die klinische Untersuchung des Auges inklusive der Augenhintergrunduntersuchung. Um diese im NKLM definierte Kompetenz bestmöglich zu trainieren, wurde an der Augenklinik der Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Firstly, studies indicated that students were satisfied with their AR and VR learning experiences. They reported that the immersive nature of this application made learning more enjoyable and interesting [11][12][13]18]. Shiels et al discovered that medical students preferred learning clinical decision-making skills in a VR simulation session over a case-based discussion [11].…”
Section: Clinical Medical Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, studies indicated that students were satisfied with their AR and VR learning experiences. They reported that the immersive nature of this application made learning more enjoyable and interesting [11][12][13]18]. Shiels et al discovered that medical students preferred learning clinical decision-making skills in a VR simulation session over a case-based discussion [11].…”
Section: Clinical Medical Studentsmentioning
confidence: 99%
“…Shiels et al discovered that medical students preferred learning clinical decision-making skills in a VR simulation session over a case-based discussion [11]. Moreover, Loidl et al showed in their study that students became more interested in the lesson and in pursuing ophthalmology as a career after completing a week-long ophthalmology module with the inclusion of an AR-based training simulator [18].…”
Section: Clinical Medical Studentsmentioning
confidence: 99%